Short-Term Clinical and Quality Outcomes Have Inconsistent Changes From a Quality Improvement Initiative to Increase Access to Physical Therapy in the Cardiovascular and Surgical ICU. (October 2019) - Tonna, Joseph E.; Johnson, Joshua; Presson, Angela; Zhang, Chong; Noren, Chris; Lohse, Bryan; Bento, Haley; Barton, Richard G.; Nirula, Raminder; Mone, Mary; Marcus, Robin
Abstract : Objectives: Studies of mobility during critical illness have mostly examined transitions from immobility (passive activities) or limited mobility to active "early mobility." Design: Observational analysis of a quality improvement initiative. Setting: Two ICUs (surgical ICU, cardiovascular ICU) at a tertiary academic medical center. Patients: Critically ill surgical and cardiovascular patients. Interventions: Doubling available physical therapy. Measurements and Main Results: We examined the outcomes of therapy time/patient/day, ICU and hospital length of stay, disposition location, and change in functional status. We adjusted for age, sex, illness severity, and number of surgeries. Among 1, 515 patients (703 baseline, 812 quality improvement), total therapy time increased from 71, 994 to 115, 389 minutes and from 42, 985 to 93, 015 minutes, respectively, in each ICU. In the cardiovascular ICU per patient therapy increased 17% (95% CI, –4.9 to 43.9; p = 0.13), and in the surgical ICU, 26% (95% CI, –1 to 59.4; p = 0.06). In the cardiovascular ICU, there was a 27.4% decrease (95% CI, –52.5 to 10.3; p = 0.13) in ICU length of stay, and a 12.4% decrease (95% CI, –37.9 to 23.3; p = 0.45) in total length of stay, whereas in the surgical ICU, the adjusted ICU length of stay increased 19.9% (95% CI, –31.6 to 108.6; p = 0.52) and total length of stay increased 52.8% (95% CI, 1.0–130.2; p = 0.04). The odds of a lower level of care discharge did not change in either ICU (cardiovascular ICU: 2.6 [95% CI, 0.6–12.2; p = 0.22]); surgical ICU: 3.6 [95% CI, 0.9–15.4; p = 0.08]). Conclusions: Among diverse cardiothoracic and surgical patients, a quality improvement initiative doubling physical therapy shifts is associated with increased total administered therapy time, but when distributed among a greater number of patients during the quality improvement period, the increase is tempered. This was not associated with consistent changes in ICU length of stay or changes in disposition location. Abstract : Supplemental Digital Content is available in the text.